2001
DOI: 10.1046/j.1365-2346.2001.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unconsciousness during a lesser occipital nerve block in a patient with the occipital bone defect

Abstract: Occipital nerve block is usually considered to be a very simple and safe regional anaesthetic technique. We describe a case of sudden unconsciousness during a lesser occipital nerve block in a patient with an occipital bone defect. A 63-year-old man complained of headache, which was localized to the right occipital region. A right lesser occipital nerve block with a local anaesthetic was performed for treatment. During the lesser occipital nerve block, the patient suddenly became disturbed and lost consciousne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…Also notable is that our patient’s prior craniectomy resulted in a skull defect, although it was minimal after repair. In the literature, there are reports of serious adverse effects after peripheral nerve blocks applied around skull defects . In this case we performed a PNB far from the skull defect without complications.…”
Section: Discussionmentioning
confidence: 92%
“…Also notable is that our patient’s prior craniectomy resulted in a skull defect, although it was minimal after repair. In the literature, there are reports of serious adverse effects after peripheral nerve blocks applied around skull defects . In this case we performed a PNB far from the skull defect without complications.…”
Section: Discussionmentioning
confidence: 92%
“…Infection or bleeding may result from any percutaneous technique, though these are usually minor problems. A case of sudden unconsciousness due to inadvertent subarachnoid injection in a patient with a craniotomy defect has been reported ( 60 ). Temporary dizziness, injection site soreness, focal alopecia, and paresthesia due to nerve injury should be anticipated ( 61 - 63 ).…”
Section: Potential Complications and Red Flagsmentioning
confidence: 99%
“…In experimental rats, the intracerebral injection of tetrodotoxin induced a similar pupillary response [ 5 ]. Okuda et al [ 6 ] reported a case of seizure caused by an incidental subarachnoid space injection. Unlike our case, the patient experienced general discomfort and nausea as well as loss of consciousness immediately after a lesser occipital nerve block, using 0.5 ml 1% mepivacaine.…”
Section: Discussionmentioning
confidence: 99%